2015
DOI: 10.1515/pjvs-2015-0012
|View full text |Cite
|
Sign up to set email alerts
|

Feeding milk replacer instead of whole milk affects blood plasma proteome and lipid profile in preruminant calves

Abstract: The study was undertaken to determine the effect of feeding milk or milk-replacer on the blood plasma proteome and lipid profile in calves during the second week of life. Feeding milk-replacer significantly decreased the expression of plasma apoA-I. Age of calves affected apoA-I expression, which was higher on the 8 th than on the 11 th and 14 th day of life. A significant effect of interaction between diet and age was also observed. The expression of apoA-IV, was significantly affected by diet and was lower i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Lepczyński et al (17) observed lower blood plasma concentrations of total cholesterol, HDL-cholesterol, and LDL-cholesterol and downregulation of apo A-IV in preruminant calves fed milk replacer in comparison to calves fed whole milk. Moreover, the authors showed that the milk replacer had a much higher carbohydrate content than the milk (17). Apolipoprotein A-IV is a glycoprotein synthesized primarily in the enterocytes of the small intestine during fat absorption.…”
Section: Discussionmentioning
confidence: 99%
“…Lepczyński et al (17) observed lower blood plasma concentrations of total cholesterol, HDL-cholesterol, and LDL-cholesterol and downregulation of apo A-IV in preruminant calves fed milk replacer in comparison to calves fed whole milk. Moreover, the authors showed that the milk replacer had a much higher carbohydrate content than the milk (17). Apolipoprotein A-IV is a glycoprotein synthesized primarily in the enterocytes of the small intestine during fat absorption.…”
Section: Discussionmentioning
confidence: 99%
“…Previous proteomic studies of calf blood plasma [30] have shown a significant reduction in apoA-IV expression on the first day, when changing from milk feeding to milk replacer. During the next days of life, the expression of this protein increased.…”
Section: Discussionmentioning
confidence: 95%
“…So, animals fed with milk have a high concentration of cholesterol, low and high density lipoproteins in the blood plasma. At the same time, the composition of the milk replacer as a fat source is the main factor influencing the synthesis of proteins important for cholesterol metabolism and the lipid profile in artificially fed calves (Lepczyński et al, 2015;Ross et al, 2021).…”
Section: Discussionmentioning
confidence: 99%